Implementasi Proyek Penguatan Profil Pelajar Pancasila dalam Kurkulum Merdeka Belajar di SMPN 1 Bulawa - Dilapanga, Muhammad Beni; Yunus, Rasyid; Adhani, Yuli (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine how the planning of implementation and evaluation, implementation of the Pancasila student profile strengthening project in the independent learning curriculum at SMP Negeri 1 Bulawa. The author uses descriptive qualitative field research, so the data collection method uses observation, interviews, and documentation when collecting data. The data analysis technique uses the method developed by. Miles and Huberman, namely reducing data, presenting data, and verifying data. The results of this study indicate that in the implementation activities of the Pancasila student profile strengthening project in the independent learning curriculum in class 7 of SMP Negeri 1 Bulawa. There is a flow 1 project planning by forming a P5 facilitator team, identifying the level of readiness of the education unit, designing the dimensions of the theme and time allocation of P5, compiling P5 modules, designing project reporting strategies. Flow 2 preparation for implementation with a project preparation meeting with the principal and teaching staff, silisanya with students, making monitoring and evaluation instruments, preparing tools and materials. The implementation consists of my experience activities, let's watch activities, discussion activities, choose trash activities, waste needs analysis activities, my trash my creativity activities, exhibition preparation activities, product demonstration activities, reflection and evaluation activities, follow-up activities. The flow of 3 evaluations consists of an assessment rubric, student reflection sheets, teacher assessment rubric evaluation sheets, dimensions of faith and piety in the one and only God and noble character, creative dimensions, report card results.